Analysis of the Integration of Environmentally Friendly Fishing Gear Technology in the Aquatic Conservation Areas of Agam Regency for the Sustainable Improvement of Fishermen's Economy - Uzra, Murhenna; Sari, Siska Fitrima; Triawan , Ade; Zahmi , April; Efendi, Gustri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The use of environmentally friendly fishing gear has been proven to have a positive impact not only on the aquatic ecosystem in the conservation areas of Agam Regency but also on the economic aspects of fishermen. The use of selective fishing gear can reduce over-exploitation of fish stocks, which ultimately creates a sustainable fisheries system. The aim of this study is to educate the use of bagan (fish trap) technology to improve the economy of fishermen in a better and more sustainable way. The method used is research development, utilizing primary and secondary data through questionnaires, surveys, and structured interviews. The results of the study indicate that the integration of this technology is also in line with the principles of blue economy and marine conservation, where the balance between utilization and preservation is the key focus. Intensive training and mentoring from government institutions, as well as multi-stakeholder collaboration, are key factors in the success of this implementation. However, the main challenge lies in the aspects of socialization and availability of tools. Further efforts in the form of continuous education and more affordable financing schemes are needed so that all fishermen can fully transition without concerns about short-term economic aspects.